2011
DOI: 10.4067/s0717-95022011000100030
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Folliculogenesis in the Smallnose Fanskate Sympterygia bonapartii (Müller & Henle, 1841) (Chondrichthyes, Rajidae)

Abstract: SUMMARY:Chondrichthyes have become an important economic resource in the last decades, with Argentina as one of the countries that exploits more sharks and skates, even at levels that exceed de limits of many species. However, there is a scarce knowledge of the reproductive biology of this group, particularly from species inhabiting the Southern hemisphere. This work shows the most relevant facts during folliculogenesis in Sympterygia bonapartii. Results show that germinal cells are present in immature and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…The anatomical disposition of the uteri of Sympterygia acuta and S. bonapartii is consistent with that seen in all studied Chondrichthyes (Díaz-Andrade et al, 2011;Galíndez et al, 2010a;Hamlett & Hysell, 1998;.…”
Section: Discussionsupporting
confidence: 85%
“…The anatomical disposition of the uteri of Sympterygia acuta and S. bonapartii is consistent with that seen in all studied Chondrichthyes (Díaz-Andrade et al, 2011;Galíndez et al, 2010a;Hamlett & Hysell, 1998;.…”
Section: Discussionsupporting
confidence: 85%
“…In these groups, the proliferative phase of oogenesis ends at birth; which is different from what it has been observed in teleosts, reptiles, and many amphibians (Lombardi, ). In other species of batoids such as Torpedo marmorata (Prisco et al, ), S. acuta (Díaz‐Andrade et al, ), and S. bonapartii (Díaz‐Andrade et al, ), oogonia in ovaries of newborn individuals have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the presence of these cells has been observed even in exemplars that were close to hatching size (Díaz-Andrade et al 2009). Likewise, this cell type may be present in maturing females (Díaz-Andrade et al, 2011;Galíndez et al, 2014). The reproductive potential of species rests, among other things, in the number of primordial germ cells that can be recruited as gametes.…”
Section: Discussionmentioning
confidence: 99%